In vivo wound Healing Activity of Ointment based Formulation for Prunus amygdalus (Batsch.) on Rats - Singh, Diksha; Gohil, Kashmira J; Sharma, Vikash; Shukla, Shiv Shankar (Indian Journal of Pharmaceutical Education and Research, 2022)
Objectives: The present study is to investigate the wound healing activity of F1-PAO and F2-PAE ointment formulations based on Prunus amygdalus oil and extract respectively. Materials and Methods: The ethanolic and n- hexane extract of Prunus amygdalus (Batsch.) Seed (Nut) was done and incorporate to make F1-PAO and F2-PAE ointments formulations. Above formulations were investigated for their wound repairing potential by excision and incision model in Albino wistar Rats. Animals were divided in five groups, each containing 6 animals. Group I (control) no treatment, Group II (Negative group) treated with simple ointment base, Group III was standard, treated with marketed formulation (Betadine). Group IV (F1-PAO) and Group V (F2-PAE) in excision and Incision model treated with ointments prepare from Prunus amygdalus (Batsch.) extract and oil. The wound healing process was examined with the naked eye until the wounds were fully healed. In excision model, wound contraction rate while, in incision model tensile strength (skin breaking strength) was observed and evaluated. The data obtained was statistically verified by using one-way ANOVA followed by Dennett’s test. Results and Discussion: Both the formulations significantly reduced the wound area and enhanced percentage of wound closure with compared to Positive control group, but healing process in F2-PAE was found to better than F1-PAO. Recent studies already suggested about the phytoconstituents present in extract formulation and oil-based formulation. Alkaloid and tannins were supposed to be present F2-PAE and responsible for better effect than F1-PAO. Conclusion: The investigation showed that both ointment formulation i.e., F1-PAO and F2-PAE treated groups have significant wound healing activitiy but F2-PAE was found to be more effective than F1-PAO.
Keywords: Prunus amygdalus (Batsch.); Almond; Wound healing; Excision; Incision